World Health Organization‐defined classification of myeloproliferative neoplasms: Morphological reproducibility and clinical correlations—The Danish experience. Issue 12 (30th September 2013) - Madelung, Ann Brinch; Bondo, Henrik; Stamp, Inger; Loevgreen, Preben; Nielsen, Signe Ledou; Falensteen, Anne; Knudsen, Helle; Ehinger, Mats; Dahl‐Sørensen, Rasmus; Mortensen, Nana Brochmann; Svendsen, Kira Dynnes; Lange, Theis; et al.
<x xml:space="preserve">Abstract</x> We examined inter‐ and intraobserver reproducibility and concordance between histological diagnosis and independently collected clinical findings in a large series of patients with the major subtypes of myeloproliferative neoplasms (MPNs) and controls. Seven hematopathologists reviewed 272 bone marrow biopsies including 43 controls. Diagnoses were determined according to the 2008 criteria of the World Health Organization (WHO). The participants were blinded to all clinical data except patient age. After initial evaluation all hematopathologists participated in a 3‐day meeting with a leading clinician chaired by an expert hematopathologists. In cases with lack of consensus on fiber grading (n = 57), a new evaluation was performed. In cases with discordance on morphological diagnosis (n = 129), an additional nonblinded evaluation taking clinical data into consideration was carried out. For remaining cases with a lack of concordance between morphological diagnosis and clinical diagnosis (n = 33), a similar nonblinded evaluation was performed. Consensus on final histological diagnosis and concordance with clinical diagnosis were determined. Blinded histological evaluation resulted in a 53% consensus rate. After re‐evaluation of fiber content, consensus was reached in 60% of cases. Adding clinical data increased the histological consensus to 83%. For cases with a histological consensus, we found a concordance of 71% with the clinician's diagnoses. This is the first study to present a larger cohort of MPN patients mimicking the diagnostic challenges that hematopathologists face in their daily practice. The results support the postulates of the WHO that both morphological and clinical findings are essential for a valid diagnosis Am. J. Hematol. 88:1012–1016, 2013. © 2013 Wiley Periodicals, Inc.